Screening of potato genotypes against common scab disease caused by Streptomyces scabies in the plains of West Bengal* - BASU, AMITAVA (The Indian Journal of Agricultural Sciences, 2011)
A field trial was conducted during 2002-04 on 12 potato cultivars for screening against common scab disease at West Bengal. None of the cultivars were found resistant although 3 cultivars namely 'Kufii Lalima', 'Kufn Sindhuri' and 'Kufri Anand' were found least susceptible. 'Kufri Sindhuri' had the least scab index during 2002-2003 and 2003-2004 of only 12.0% and 11.0% respectively. Three cultivars, ie 'Kufri Jyoti', 'Kufri Chandrarnukhl' and 'Kufri Ashoka' were found to be highly susceptible. The remaining cultivars were either moderately susceptible or susceptible. Earlier, red skinned cultivar 'Kufri Sindhuri' was reported to be less susceptible to scab disease (Singh and Singh 1992). In general, it was observed that red skinned cultivars were least susceptible to this pathogen as compared to white skinned cultivars except 'Kufri Anand'. It may be stated that, quality of potato is a vital factor nowadays and qualitative losses of potatoes due to scab disease may be minimized if the cultivars like 'Kufri Lalima', 'Kufri Sindhuri' and 'Kufii Anand' are extensively utilized for this agroclimatic region of West Bengal.